Procedural Scripts in YouTube Tutorial Videos as a Learning Tool for Writing in Junior High School - Aulia Rahayu; Herman Budiyono (LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2026)
This study aims to analyze (1) the structure of procedural texts, (2) the linguistic features used, and (3) the feasibility of YouTube tutorial videos as learning media for teaching procedural text writing in junior high school. This research employed a qualitative approach with a content analysis method. The data sources consisted of 13 tutorial videos from the Kreasi Aiswa YouTube channel published in January 2026. The data were collected through documentation, observation, note-taking, and transcription techniques. The analysis was conducted using an interactive model involving data reduction, data display, and conclusion drawing. The results show that all videos generally contain the main structure of procedural texts, namely introduction, body, and closing, although the completeness varies. Most videos (69.2%) are categorized as appropriate, while 30.8% are less appropriate, mainly due to the absence of brief overviews and closing explanations. In terms of linguistic features, the majority of videos (69.2%) are appropriate and 30.8% are highly appropriate, with consistent use of imperative sentences, temporal conjunctions, and material verbs, although the use of sequence markers is not always systematic. Regarding feasibility, 69.2% of the videos are categorized as feasible and 30.8% as highly feasible as learning media. In conclusion, YouTube tutorial videos have strong potential as instructional media for procedural text writing, but they require careful selection and pedagogical reinforcement by teachers to optimize their use in classroom learning.